A panchromatic view of infrared quasars: excess star formation and radio emission in the most heavily obscured systems. Issue 2 (3rd October 2022) - Andonie, Carolina; Alexander, David M; Rosario, David; Laloux, Brivael; Georgakakis, Antonis; Morabito, Leah K; Villforth, Carolin; Avirett-Mackenzie, Mathilda; Rivera, Gabriela Calistro; Del Moro, Agnese; Fotopoulou, Sotiria; Harrison, Chris; et al.
ABSTRACT: To understand the active galactic nuclei (AGNs) phenomenon and their impact on the evolution of galaxies, a complete AGN census is required; however, finding heavily obscured AGNs is observationally challenging. Here we use the deep and extensive multiwavelength data in the COSMOS field to select a complete sample of 578 infrared (IR) quasars (L_AGN, IR10^45\: erg\: s^-1 ) at z < 3, with minimal obscuration bias, using detailed UV-to-far-IR spectral energy distribution (SED) fitting. We complement our SED constraints with X-ray and radio observations to further investigate the properties of the sample. Overall, 322 of the IR quasars are detected by Chandra and have individual X-ray spectral constraints. From a combination of X-ray stacking and L_2-10 kev – L_6\: μ m analyses, we show that the majority of the X-ray faint and undetected quasars are heavily obscured (many are likely Compton thick), highlighting the effectiveness of the mid-IR band to find obscured AGNs. We find that 355 (≈61 per cent) IR quasars are obscured (N_H10^22\: cm^-2 ) and identify differences in the average properties between the obscured and unobscured quasars: (1) obscured quasars have star formation rates ≈3 times higher than unobscured systems for no significant difference in stellar mass and (2) obscured quasars have stronger radio emission than unobscured systems, with a radio-loudness parameter ≈ 0.2 \: dex higher. These results are inconsistent with a simple orientation model but in general agreement with either extreme host-galaxy obscuration towards the obscured quasars or a scenario where obscured quasars are an early phase in the evolution of quasars.